Mindfulness moments for clinicians in the midst of a pandemic - Hedderman, E. (Ir J Psychol Med, 2020)
Clinicians are routinely subjected to intense and stressful working environments, and the current COVID-19 crisis increases their risk of psychological distress. Mindfulness has been shown to improve life satisfaction, resilience to stress, self-compassion, compassion and general well-being in healthcare workers. Based on their clinical experience, the authors present mindfulness moments for clinicians (MMFC), a selection of short, simple and accessible mindfulness practices to promote resilience and compassion among clinicians working in this pandemic. The practices can be used on the job and are accessible to both novice and experienced meditators. Most of these practices are extracted from evidence-based mindfulness programmes. Further research is indicated to assess the effectiveness of using MMFC to support clinicians in their work and to promote resilience.